Growth performance of food and beverage industry in India: a fresh look using structural break approach. (11th April 2022) - Pal, Soma; Chakraborty, Chandrima
The present study is an attempt to look into the growth performance of the food and beverage industry in India for an extensive period of almost four decades from 1980-1981 to 2017-2018 employing the endogenous structural break approach of Sen (2003). Along with it, the growth enhancing factors are also tried to be identified. The result suggests that the rate of growth is not uniform over the sample period. Rather there exists a structural break in the year 2007-2008 which may be the outcome of Vision 2015 of the Ministry of Food Processing Industry, 2005. After the break, growth has considerably increased. While detecting the factors enhancing output growth, a nonlinear relationship is found. Output growth may be stimulated by increasing firm size, higher degree of mechanisation, achieving the right composition of work-force and upsurge in relative wage rate. Furthermore, export intensity is found to dominate over import intensity in encouraging output growth.